2021
DOI: 10.3390/ma14195886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microstructure and Mechanical Properties of High Strength and Toughness Ship Plate Steel

Abstract: E36 ship plate steel was, respectively, produced by as rolling and normalizing process (ARNP), and EH36 and FH36 ship plate steel was produced by the thermo-mechanical control process (TMCP) with low carbon and multi-element micro-alloying. The microstructure of the three grades of ship plate steel was composed of ferrite, pearlite, and carbides at room temperature. The average grain size on 1/4 width sections (i.e., longitudinal sections) of the three grades of ship plate steel was, respectively, 5.4 μm, 10.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Figure 10 shows the OM images of the steel plate at the surface, 1 4 thickness and 1 2 thickness for RD-TD section. It can be seen from the images that the microstructure was mainly composed of polygonal ferrite (Pα), acicular ferrite (Aα) and granular bainite (GB) at the surface, in which there was Pα, a small amount of Aα and GB at 1 4 thickness and Pα and a small amount of pearlite (P) and GB at 1 2 thickness. The pearlite was formed due to the smaller deformation and slower cooling at the 1 2 thickness of the plate, which allowed sufficient time for the diffusion of alloy and carbon elements into the high-density region of dislocations in the deformation zone.…”
Section: Element Content Variation In Different Phasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 10 shows the OM images of the steel plate at the surface, 1 4 thickness and 1 2 thickness for RD-TD section. It can be seen from the images that the microstructure was mainly composed of polygonal ferrite (Pα), acicular ferrite (Aα) and granular bainite (GB) at the surface, in which there was Pα, a small amount of Aα and GB at 1 4 thickness and Pα and a small amount of pearlite (P) and GB at 1 2 thickness. The pearlite was formed due to the smaller deformation and slower cooling at the 1 2 thickness of the plate, which allowed sufficient time for the diffusion of alloy and carbon elements into the high-density region of dislocations in the deformation zone.…”
Section: Element Content Variation In Different Phasesmentioning
confidence: 99%
“…Figure 12c,f shows that there was only a small amount of GB at ½ thickness. 1 4 thickness and (c) 1 2 thickness.…”
Section: Element Content Variation In Different Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding research on different types of ship plate steel, differences in their performance have been observed. Taking EH36 and FH36 ship plate steel as examples, Wang et al [3] assessed the fatigue crack propagation rates of EH36, DH36, and FH36 ship plate steels at 2 of 23 room temperature, and found that EH36 steel had a higher fatigue crack propagation rate than the other steel types due to its higher carbon content and smaller grain size.…”
Section: Introductionmentioning
confidence: 99%
“…), which is not the case for other methods [5][6][7][8][9]. This feature is due to a special mechanism for the formation of fine-grained steel microstructures during phase transformations under rapid cooling conditions in combination with the deformed structure of the initial phase [4,10]. It is extremely difficult to achieve such a microstructure using other technological solutions (for instance, by microalloying) without controlled cooling.…”
Section: Introductionmentioning
confidence: 99%